2010
DOI: 10.1016/j.tet.2010.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-imidazolinium carbene-catalyzed arylation of aldehydes with arylboronic acids in water

Abstract: Abstract. The catalytic arylation of aldehydes with arylboronic acids in only water was found to be achieved using the palladium/thioether-imidazolinium chloride system in good to excellent yields. This catalytic process showed high tolerance for a broad range of substrates, giving a variety of carbinol derivatives with 2.0-3.0 mol % of the catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Based on the positive results obtained for the benzhydrols, the newly developed methodology was applied to the more challenging carbohydrate substrates. It should be noted that many of the previous methodologies for the preparation of glycosyl azides rely on Mitsunobu‐like conditions with metal azides and hydrazoic acid or by the reaction of unstable glycosyl halides with sodium azide . Remarkably, the conditions used for the benzhydrols led to a 67 % yield with an α/β ratio of 3.3:1 when applied to 2,3,5‐tri‐O‐benzyl‐ β ‐D‐arabinofuranose.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the positive results obtained for the benzhydrols, the newly developed methodology was applied to the more challenging carbohydrate substrates. It should be noted that many of the previous methodologies for the preparation of glycosyl azides rely on Mitsunobu‐like conditions with metal azides and hydrazoic acid or by the reaction of unstable glycosyl halides with sodium azide . Remarkably, the conditions used for the benzhydrols led to a 67 % yield with an α/β ratio of 3.3:1 when applied to 2,3,5‐tri‐O‐benzyl‐ β ‐D‐arabinofuranose.…”
Section: Resultsmentioning
confidence: 99%
“…(4‐Formylphenyl)(phenyl)methanol (S6): The title compound was prepared from 4‐(diethoxylmethyl) benzaldehyde (300 mg, 1.44 mmol, 1.0 eq.) and phenylmagnesium bromide (391 mg, 2.16 mmol, 1.5 eq.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above-mentioned additions of diverse boronic acids to activated and non-activated double bonds, more traditional 1,2-addition reactions with C-heteroatom double bonds have been described. Thus, the organocatalytic formylation of boronic acids with glyoxylic acid [199], the palladium-imidazolinium carbene-catalyzed arylation of aldehydes with boronic acids [200], the rhodium-catalyzed addition of boronic acids to 2,2-disubstituted malononitriles [201,202], the rhodium-catalyzed addition of boronic acids to α-ketoesters [203], and the addition of boronic acids to nitrosoarenes [204] are all valuable examples.…”
Section: Chemical Transformations Of Indolylboronic Acid Derivativesmentioning
confidence: 99%
“…Then, only thioether-imidazolinium chloride 6e was proven to be an effective N-heterocyclic carbene ligand precursor (entries 1-6). 45) Evaluation on the effect of organic solvents revealed that smooth reaction progress required appropriate solvent polarity (entries 7-9). Interestingly, dimethyl sulfoxide (DMSO) gave a quite poor result although the reaction in more highly polar water proceeded efficiently, which could be achieved by hydrophobic effects.…”
Section: Palladium-catalyzed 12-addition Of Organoboronic Acids To Amentioning
confidence: 99%